Analisis Pembiayaan pada Program Kesehatan Ibu dan Anak Melalui Metode Health Account di Kabupaten Jember - Armahedi, Geofani; Witcahyo, Eri (Jurnal Ekonomi Kesehatan Indonesia, 2020)
Maternal and Child Health (MCH) is unresolved health problems in Indonesia. Mother and child are family members who need attention and priority in delivery of health. In 2012, there were six provinces that were focus of government in resolve problems of maternal mortality, one of them was East Java. Jember District is one of district in East Java that is still having problems with MCH. The addition of the budget in increasing maternal and child health has not been running optimally in Jember. Therefore, it is necessary to research with Health Account approach related to MCH in Jember District. This type of research was descriptive research. The unit of analysis in this research was the institution that carried out direct or indirect activities on the MCH program in 2018 with an appropriate budget focus at the regional level. The results of research showed that expenditure patterns on every program were widely used for investment expenditure and the budget was prioritized for investment expenditure in indirect activities. The advice given is that Jember District Government develops policies directed at healthy paradigm development and builds an integrated financial management information system, and must also create a legal protection to institutionalize implementation of Health Accounts at distrcit level.